Electrical Injury (a Literature Review) - E. A. Zhirkova; T. G. Spiridonova; A. V. Sachkov; K. V. Svetlov (Неотложная медицинская помощь)
The analysis of domestic and foreign literature sources showed that the problem of diagnosing and treating electrical injuries remained relevant as in the early 20th century. Over the past century, the mechanisms of the effects of electric current on organs and tissues have been well studied. However, the search for methods for diagnosing the volume of tissue damage has not been completed, and such methods are necessary, since they are designed to help determine the volume of surgical intervention. Many patients still require repeated surgical interventions to completely excise necrotic tissue. In most patients with severe electrical trauma, reconstructive surgery takes place in several stages. Today, most clinical data and practical recommendations are based on the opinions of individual experts and limited clinical studies.Authors declare lack of the conflicts of interests.